2022
DOI: 10.3390/polym14214609
|View full text |Cite
|
Sign up to set email alerts
|

Permittivity and Dielectric Loss Balance of PVDF/K1.6Fe1.6Ti6.4O16/MWCNT Three-Phase Composites

Abstract: New three-phase composites, destined for application as dielectrics in the manufacturing of passive elements of flexible electronics, and based on polymer (PVDF) matrix filled with powdered ceramics of the hollandite-like (KFTO(H)) structure (5.0; 7.5; 15; 30 vol.%) and carbon (MWCNT) additive (0.5; 1.0; 1.5 wt.% regarding the KFTO(H) amount), were obtained and studied by XRD, FTIR and SEM methods. Chemical composition and stoichiometric formula of the ceramic material synthesized by the sol–gel method were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…A change in the quantitative ratio of the filler/matrix was noted both in the X-ray diffraction patterns and in the FTIR spectra Optimization of the values of the dielectric constant and the dielectric loss tangent is the main task for creating composite dielectrics with a polymer matrix. Previously, we used the ε ′ -tanδ diagram [66] to analyze the balance of dielectric properties. The diagram is divided by a straight line described by equation ε = 76.6 log(tanδ) + 153.2 from a recently published paper [78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A change in the quantitative ratio of the filler/matrix was noted both in the X-ray diffraction patterns and in the FTIR spectra Optimization of the values of the dielectric constant and the dielectric loss tangent is the main task for creating composite dielectrics with a polymer matrix. Previously, we used the ε ′ -tanδ diagram [66] to analyze the balance of dielectric properties. The diagram is divided by a straight line described by equation ε = 76.6 log(tanδ) + 153.2 from a recently published paper [78].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent publications report that hollandite-like solid solution ceramics can exhibit high dielectric constants (ε ′ = 10 3 -10 4 ) [61,62], which also makes them attractive materials as ceramic fillers for high dielectric polymer composites. Previously, hollandite-like solid solutions K x Ti 8-y Me y O 16 (Me = Cu, Ni, Fe) were studied as fillers for PMMA, Epoxy, PVDF, and PTFE matrices [63][64][65][66]; however, these composites demonstrated an increase in dielectric constant and strong increase in dielectric losses. An effective way to inhibit dielectric losses in the case of PTFE and PVDF polymer matrices was to use a three-phase strategy in the preparation of composites.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain Ti 3 AlC 2 MAX phase powder, the molten salt shielded synthesis in open air technique was used, similar to the previously described methods. 34,35 TiC (550 mesh, 99.6%, Sichuan Porous Metal Technology Co., Ltd), Ti (400 mesh, 99.9% Sichuan Porous Metal Technology Co., Ltd), and Al (120 mesh, Chengdu WOCO Carbide Industry Co., Ltd) powders were used as reagents. First, the powders were mixed in a stoichiometric molar ratio of 2 : 1 : 1.4 (TiC : Ti : Al) in a PLANETARY MONO MILL Fritsch PULVERISETTE 6 at 300 rpm for 30 min using ZrO 2 balls with 4 mm diameter.…”
Section: Synthesis and Exfoliation Of The Ti 3 Alc 2 Max Phasementioning
confidence: 99%
“…Therefore, the composites filled with two or more types of fillers have been explored [19,20]. By introducing Ag-coated ceramic filler K 2 Ni 0.93 Ti 7.07 O 16 (KNTO) into polyvinylidene fluoride (PVDF), the dielectric constant of 2.5 wt% KNTO @ Ag/PVDF composites was 1.62 times that of KNTO-PVDF and 2.59 times of pure PVDF film [21]. Huanhuan Zhang [22] reported that the addition of two-dimensional organic modified montmorillonite (OMMT) into CNT/PVDF composites can prevent the formation of CNT conductive pathways and allow electrons to move freely in CNT clusters within a short distance.…”
Section: Introductionmentioning
confidence: 99%